Pendidikan Agama Islam Berbasis Teknologi (AI) Artificial Intelligence - Fitri Sarinda; Martina Martina; Dwi Noviani; Hilmin Hilmin (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This research aims to discuss Islamic religious education based on AI (Artificial Intelligence) technology. The results of this research show that current technological developments are very rapid, especially artificial intelligence AI (Artificial Intelligence) has had a big impact on the education sector, especially in Islamic religious education, IA (Artificial Intelligence) technology makes it easier for educators to deliver interesting teaching materials and methods. , so that students do not feel bored and bored, can improve the quality of the teaching and learning process to be more active and innovative, measure student understanding, and accelerate students' understanding of Islamic religious education. Through AI (Artificial Intelligence) technology such as visual mentors, Voice Assistants such as Google Assistant, Siri, and Cortana and Presentation Translator. The approach in this research uses a qualitative approach with the library research method. Researchers obtain data from various sources including journals, books, articles and others.